Klippel Trenaunay Syndrome: A Brief Overview - Pande Ayu Naya Kasih Permatananda; I Gusti Agung Made Adnyana Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Klippel-Trenaunay syndrome is a rare congenital vascular disease. The pathogenesis of this syndrome is unclear, but it is thought that most cases are the result of somatic mutations that affect genes that play a role in vasculogenesis and angiogenesis. Some patients come with a triad of capillary malformation (hemangioma or port-wine stain), venous varicosities and bony or soft tissue hypertrophy. Clinical presentation of this syndrome can lead to significant morbidities and mortalities due to severe bleeding and emboli. Although the number of cases is low, a doctor must be able to distinguish Klippel-Trenaunay Syndrome from other rare vascular disorders. Parkes Weber syndrome is usually similar to Klippel-Trenaunay syndrome, except in the arterial malformations associated with capillary malformations and soft tissue to skeletal or bone hypertrophy. The diagnosis of Klippel-Trenaunay Syndrome is carried out clinically and is quite difficult to do even with experienced doctors because there is no precise pathognomonic test. There are several options in relation to the management of Klippel-Trenaunay Syndrome and non-invasive procedure is considered to be the most important of therapy modalities. Early diagnoses, progression monitoring, and proper intervention should be carried out for better prognosis and preventing complication.